A High Throughput Serum Paraoxonase Assay for Discovery of Small Molecule Modulators of PON1 Activity - Graves, Tiffany L (Bentham Open, 2008)
PON1 has been demonstrated to be the serum enzyme responsible for detoxifying organophosphate chemical weapons and plays a protective role against atherosclerosis. In order to identify small molecules that modulate PON1 activity in serum, we developed a high throughput kinetic absorbance assay using mouse serum and the organophosphate paraoxon. The IC(50) value obtained for the known PON1 inhibitor, 2-hydroxyquinoline, matched the value reported for purified PON1. A compound library was screened resulting in no confirmed activators, but 12 confirmed inhibitors. Seven of these hits also inhibited purified human PON1. One compound was only two-fold less potent than 2-hydroxyquinoline in the serum assay, but 10-fold more potent against purified PON1. This compound (IC(50) = 420 nM) may be useful towards a chemical probe for PON1. Therefore, this assay has utility as a high throughput assay for discovery of small molecule modulators of PON1 activity that maintain activity in serum.